Changes in pediatric fracture patterns presenting to US emergency departments before, during, and after the COVID-19 pandemic - Randall T. Loder; Benjamin A. Johnson (Heliyon, 2023)
The purpose of this study was to analyze the demographics of pediatric fracture patients before, during, and after the COVID pandemic using US national emergency department (ED) data. The National Electronic Injury Surveillance System (NEISS) data for the years 2018 through 2021 was extracted for those <16 years of age, and organized into 24 consecutive bimonthly groups. There was a decrease in the number of ED visits for fractures in 2020 and returned to pre-COVID levels by March/April of 2021, except for small hospitals which demonstrated an earlier rebound beginning in late 2020. During the pandemic the incident locale was more frequently the home and less at schools/sporting venues, which returned to pre-COVID levels by March/April 2021. The proportion of those not discharged from the ED increases from March/April 2020 to March/April 2021. The median age was 8.8, 9.0, 8.2, and 8.7 years respectively for the years 2018, 2019, 2020, and 2021. Early in the pandemic there were more radius/ulna and fewer finger fractures and more tibia/fibula and fewer toe fractures; these changes did not return to pre-COVID percentages until the end of 2021. Fractures associated with bicycles and trampolines remained stable throughout the pandemic, those due to skateboards increased, and those due to playground and sporting activities decreased, with varying times of return to pre-COVID levels. In conclusion pediatric fracture patterns during the COVID-19 pandemic demonstrated many changes; most returned to baseline patterns by early/mid 2021 except for small hospital EDs which saw a much quicker rebound by late 2020. This national data gives health care providers/administrators information about what can happen during a modern day pandemic. If another pandemic occurs in the future mandating lockdowns, this data may be useful to guide resource and manpower allocations.